DIAGNOSTIC AND MANAGEMENT PROBLEMS OF HYPERTHYROIDISM IN A PATIENT WITH TESTICULAR SEMINOMA - Dicky Febrianto; Hermina Novida (Universitas Airlangga, 2022)
Patients with thyroid dysfunction are well represented in the general population. Hyperthyroidism can develop as a paraneoplastic syndrome in germ cell tumors. Testicular seminoma as a form of germ cell tumors, can express human chorionic gonadotropin (hCG). Beta-hCG strongly resembles TSH. A 26-year-old male with a history of cryptorchidism, came to Dr. Soetomo Hospital with the complaints of palpitation, diarrhea, weight loss, fatigue, nervousness, excessive sweating, and heat intolerance. He also complained of enlarged breast and a palpable mass in lower abdomen for 4 months. From the TSH and FT4 examinations, patient’s symptoms were in accordance with thyrotoxicosis. Anti-TPO and thyroid USG examination were within normal limits. Patient was treated with beta-blocker and thiamazole. Histopathology of abdominal mass showed a testicular seminoma. After surgery and chemoterapy, the clinical symptoms of hyperthyroidism gradually improved. Administration of beta-blocker and thiamazole was stopped in 4 months after surgery. Many of germ cell tumors in male are associated with cryptorchidism, half of them being testicular seminoma. Seminoma expresses hCG. At very high levels, hCG can stimulate the TSH receptors, causing hyperthyroidism or thyrotoxicosis. TSH and FT4 measurement were needed in patient with suspected hyperthyroidism. Anti-TPO test is performed to exclude autoimmune cause of thyroid disease. Symptomatic management of beta-hCG induced hyperthyroidism is not different from hyperthyroidism in general, namely administration of beta-blocker and anti-thyroid drugs. However, the definitive treatments are surgery and chemotherapy. Hyperthyroidism in germ cell tumors almost all responds well to surgery and chemotherapy.